The Influence of Restructuring and Competency Through Work Commitment on Employee Performance - Fakhrul Razy; M. Zahari; Sudirman Sudirman (Greenation International Journal of Economics and Accounting, 2025)
The process of using the science or art of effectively and efficiently arranging or managing natural resources and other resources is known as human resource management.  The objective is to plan, carry out, organize, and finish a variety of tasks pertaining to the supply of resources in order to accomplish predefined objectives. The purpose of this study is to characterize restructuring, competency, work commitment, and employee performance, as well as to examine how work commitment affects restructuring and competency. This study was conducted at the Sultan Thaha Saifuddin Rectorate State Islamic University in Jambi, Indonesia.   Both primary and secondary data were used in this investigation.   The sample consisted of 77 respondents.  The sample strategy used was proportional stratified random sampling. Both descriptive and quantitative analytical methods were used. In the quantitative investigation, the Partial Least Squares (PLS) approach was used for path analysis. SmartPLS 3.0 software facilitated data processing. The descriptive analysis's findings show that the State Islamic University of Sultan Thaha Saifuddin Jambi's Rectorate was judged suitable for restructuring. At the Rectorate of UIN Sulthan Thaha Saifuddin Jambi, restructuring and competency both have a favorable and considerable impact on employee job dedication, according to verification study. Both job commitment and competence were found to have a good and considerable impact on employee performance.  Restructuring did not, however, appear to have a major direct impact on worker performance.  However, when increased job dedication was used as a mediating construct, restructuring still had a favorable and substantial effect on worker performance. As a result, work dedication serves as a mediating factor that amplifies the impact of competency and restructuring on worker performance.  Therefore, improving competency and job dedication with the help of suitable organizational restructuring is a more effective way to boost employee performance.